Love and longing - Zima, Peter V. (Primerjalna književnost, 2016)
The article examines the differences between love and longing. Although both emotions are erotic in character, they differ substantially in that love is directed towards an object, whereas longing is of narcissistic origin and is directed towards the subject itself. The narcissistic subject avoids the apparently desired object because the latter is unconsciously associated with the child's early desire for the mother who is inaccessible: i.e. prohibited by the incest taboo. As the object is avoided, the desire becomes an end in itself and turns into a desire for desire's sake. It will be shown that this kind of desire - referred to as "longing" - is dominant in the works of romantic authors such as Novalis and Nerval and reappears in Baudelaire's pre-modernist poetry and in the modernist novels of Marcel Proust and James Joyce.
Keywords: Novalis, 1772-1801; Nerval, Gérard de, 1808-1855; Baudelaire, Charles, 1821-1867; Proust, Marcel, 1871-1822; Joyce, James, 1882-1941; književnost; literature; psihoanaliza; Romanticism; romantika; modernizem; ljubezen; love; hrepenenje; imagnarno; prepoved incesta; narcizem